Capital Structure Conditions Affected by Company Internal Factors: a Case Study of Non-Cyclicals Consumer Companies on Indonesian Stock Exchange - Isnaeni Rokhayati; Nirmala Nirmala; Wisnia Trias Oktaviani (J-MAS (Jurnal Manajemen dan Sains), 2021)
The purpose of this research is to find out how the variables of firm size, asset structure, profitability, liquidity, and sales growth influence the capital structure of non-cyclical consumer companies listed on the Indonesia Stock Exchange. The population in this study was 55 non-cyclical consumer companies listed on the Indonesia Stock Exchange in 2015 - 2019, while for the method of determining the sample in this study using a purposive sampling technique, as many as 25 companies. The analytical technique used is multiple linear regression analysis with panel data using the Eviews 9 program. The results show that the variables of firm size, asset structure, profitability, liquidity and sales growth have a negative and significant effect on capital structure. These results indicate that the variables of firm size, asset structure, level of profitability, liquidity and sales growth have increased, it will cause the level of the company's capital structure to decrease. Contribution to this research is expected that the company can increase company size, asset structure, profitability, liquidity and sales growth so that the use of debt in the company's capital structure decreases. This study only examines five independent variables, namely firm size, asset structure, profitability, liquidity, and sales growth. This study focuses only on examining Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange (IDX). Future research is expected to be able to add other variables that affect the capital structure by using company external variables such as taxes, economic conditions, interest rates with research objects in other companies, as well as with a longer research period so that the results obtained can be generalized.